The perception of the other for identity-building: the construction of a threat through the American identity. - Maffei, Michelle (Ánima, 2022)
The concept of threat is a wide concept to embrace because it can be associated with something unknown or something evil. However, the main idea of the concept is that it produces an existential fear. Hence, it must be eliminated or at least tried to be eliminated. These assumptions are quite limited because they cannot apprehend the polarity of things. The concept of threat and identity even though they seem mutually exclusive, are in reality mutually sustaining. Hence, this qualitative article shall argue that there is an existential need to have a threat or fear of the unknown for the construction of a strong identity. It explores the need to have a threat as a scapegoat and how these sorts of threats are pivotal to categorially understand our own identity.